The s-d exchange model as the underlying mechanism of magnetoresistance in ZnO doped with alkali metals - Zapata, C. (2019)
Fil: Nieva, G. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina